MEMPERTAHANKAN RUANG HIDUP KONSERVASI DAN BUDAYA DI TELUK TOMINI - Basri Amin (LIPI Press, 2014)
The coastal area of Pohuwato, Tomini Bay, degrades, in which the mangrove forests has been converted into fishpond. During the last ten years, the mangrove forest has widely converted into fishfond. The expansion of fishpond area is widely due to the presence of migrants fom South Sulawesi. The process is not simple, in which the locals formerly rent it to the migrants and eventually sell it to them. Uniquely, the migrants’ economic ethos in fishfond activities is well-recognized by the locals. The empowerment of coastal community, therefore, should consider the diversity of their jobs, culture, and livelihood. This paper examines the development of migrants’ economic expansion in the coastal area of Tanjung Panjang, Pohuwato. Keywords: migrant, fishpond, Tanjung Panjang, economic culture, Pohuwato, Tomini Bay